The IRE1α Arm of UPR Regulates Muscle Cells Immune Characters by Restraining p38 MAPK Activation - Gu, RuiCai; Huang, Tao; Xiao, JiangWei; Liao, ZhaoHong; Li, JunHua; Lan, HaiQiang; Ouyang, Jun; Hu, JiJie; Liao, Hua (Frontiers in Physiology, 2019)
Skeletal muscle repair and systemic inflammation/immune responses are linked to endoplasmic reticulum stress (ER stress) pathways in myopathic muscle, and muscle cells play an active role in muscular immune reactions by exhibiting immunological characteristics under persistent proinflammation stimuli. Whether ER stress affects the intrinsic immunological capacities of myocytes in the inflammatory milieu, as it does to immune cells, and which arms of the unfolded protein response (UPR) mainly participate in these processes remain mostly unknown. We investigated this issue and showed that inflammatory stimuli can induce the activation of the protein kinase R (PKR)-like endoplasmic reticulum kinase (PERK) and inositol-requiring enzyme 1α (IRE1α) arms of the UPR in myocytes both in vivo and in vitro. UPR stressor administration reversed the increased IFN-γ-induced expression of the MHC-II molecule H2-Ea, the MHC-I molecule H-2Kb, toll-like receptor 3 (TLR3) and some proinflammatory myokines in differentiated primary myotubes in vitro. However, further IRE1α inhibition thoroughly corrected the trend in the UPR stressor-triggered suppression of immunobiological molecules. In IFN-γ-treated myotubes, dramatic p38 MAPK activation was observed under IRE1α inhibitory conditions, and the pharmacological inhibition of p38 reversed the immune molecule upregulation induced by IRE1α inhibition. In parallel, our coculturing system verified that the ovalbumin (OVA) antigen presentation ability of inflamed myotubes to OT-I T cells was enhanced by IRE1α inhibition, but was attenuated by further p38 inhibition. Thus, the present findings demonstrated that p38 MAPK contributes greatly to IRE1α arm-dependent immunobiological suppression in myocytes under inflammatory stress conditions.